The maternal and perinatal implications of hypertensive disorders of pregnancy in a multiple pregnancy cohort. (20th January 2020) - Hayes‐Ryan, Deirdre; Meaney, Sarah; Hodnett, Aoibhin; Geisler, Minna; O'Donoghue, Keelin
Abstract: Introduction: Hypertensive disorders of pregnancy are common and may result in increased maternal and neonatal morbidity and mortality. Multiple pregnancies confer an increased risk of development of a hypertensive disorder of pregnancy. The purpose of this study was to examine a large cohort of women delivering a multiple pregnancy in a single large tertiary unit, and to evaluate the implications of hypertensive disorders of pregnancy on both maternal and perinatal outcomes. Material and methods: Retrospective study of all twin pregnancies delivered at Cork University Maternity Hospital, Ireland over a 9‐year period (2009‐2017). The twin pregnancies were divided according to the presence or absence of hypertensive disorder of pregnancy and the two groups were compared. Results: Maternal age >40 years, nulliparity, conception through use of a donor oocyte, and presence of obstetric cholestasis are all risk factors for the development of hypertensive disorders of pregnancy in women with a multiple pregnancy. When a hypertensive disorder complicates a twin pregnancy, it increases the incidence of iatrogenic late prematurity and neonatal hypoglycemia. Conclusions: This study is informative for clinicians caring for women with a multiple pregnancy with its relevant data on perinatal outcomes following a diagnosis of hypertensive disorder in pregnancy.